VTS in the English language classroom in Sweden - Shaun Nolan (Educare)
The position in this paper is that Visual Thinking Strategies (VTS) are very relevant for children’s education in Sweden, and that their practice makes them highly adaptable to English language teaching. The rationale for this position is that this elicitation and communication technique has proven very effective in nurturing the abilities and skills which are identified in the Swedish curriculum for compulsory schooling. The impact of VTS in the Swedish education system could be significant. First, once known and understood by teachers, VTS can be a very efficient technique in the English language classroom and can directly help to fulfil several of the ambitions of the curriculum and the English language syllabus. Second, abilities and sensitivities developed by VTS correspond to the core values of Swedish society in its promotion of democratic values, which are espoused in the compulsory school curriculum. Third, VTS lends itself to being actively used across school subjects and therefore supports an interdisciplinary sensitivity in students. VTS can help student performance and confidence across subject areas, thus again fulfilling the wider ambitions of the compulsory school curriculum and encourage these students in their growing independence as individuals and as active members of society.